Current Guideline Risk Stratification and Cardiovascular Outcomes in Chinese Patients Suffered From Atherosclerotic Cardiovascular Disease - Li, Sha; Liu, Hui-Hui; Guo, Yuan-Lin; Zhu, Cheng-Gang; Wu, Na-Qiong; Xu, Rui-Xia; Dong, Qian; Qian, Jie; Dou, Ke-Fei; Li, Jian-Jun (Frontiers in Endocrinology, 2022)
Background and aims: Heterogeneity exists among patients with atherosclerotic cardiovascular disease (ASCVD) with regard to the risk of recurrent events. Current guidelines have definitely refined the disease and we aimed to examine the practicability in Chinese population. Methods: A cohort of 9944 patients with ASCVD was recruited. Recurrent events occurred during an average of 38.5 months’ follow-up were collected. The respective and combinative roles of major ASCVD (mASCVD) events and high-risk conditions, being defined by 2018 AHA/ACC guideline, in coronary severity and outcome were studied. Results: The number of high-risk conditions was increased with increasing number of mASCVD events (1.95±1.08 vs. 2.16±1.10 vs. 2.42±1.22). Trends toward the higher to the highest frequency of multi-vessel coronary lesions were found in patients with 1- (71.1%) or ≥2 mASCVD events (82.8%) when compared to those without (67.9%) and in patients with 2- (70.5%) or ≥3 high-risk conditions (77.4%) when compared to those with 0-1 high-risk condition (61.9%). The survival rate was decreased by 6.2% between none- and ≥2 mASCVD events or by 3.5% between 0-1 and ≥3 high-risk conditions. Interestingly, diabetes was independently associated with outcome in patients with 1- [1.54(1.06-2.24)] and ≥2 mASCVD events [1.71(1.03-2.84)]. The positive predictive values were increased among groups with number of mASCVD event increasing (1.10 vs. 1.54 vs. 1.71). Conclusion: Propitious refinement of ASCVD might be reasonable to improve the survival. Concomitant diabetes was differently associated with the incremental risk among different ASCVD categories, suggesting the need of an appropriate estimate rather than a ‘blanket’ approach in risk stratification.